2019
DOI: 10.1200/jco.2019.37.31_suppl.106
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to oral medication adherence in adults with acute myeloid leukemia (AML).

Abstract: 106 Background: AML is a disease of older adults (median age 67 years). Although standard AML treatment is intravenous (IV) chemotherapy, availability of oral anti-cancer medications has increased , providing benefits and risks to patients. Patients prefer their convenience, absence of IV infusions, potential for fewer clinic visits, and increased subjective feeling of control over their disease. Poor adherence can increase toxicity risk and compromise treatment effectiveness. We aim to identify barriers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In our case, snowball sampling involved asking individuals who had completed the study to refer us to others or to post an announcement in their local patient support groups on our behalf. These additional recruiting efforts enabled us to meet our recruitment goal of 18 total participants, which is similar to the number of patients enrolled in other qualitative studies [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 86%
“…In our case, snowball sampling involved asking individuals who had completed the study to refer us to others or to post an announcement in their local patient support groups on our behalf. These additional recruiting efforts enabled us to meet our recruitment goal of 18 total participants, which is similar to the number of patients enrolled in other qualitative studies [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 86%
“…Our study's focus on implementation of technologically enabled pillboxes at the time of hospital discharge adds to existing qualitative studies in the ambulatory setting. 19,22,[27][28][29][30][31][32][33][34][35][36] These studies have examined the use of a smart pillbox in a variety of geographic locations (e.g., U.S. academic medical centers, clinics in sub-Saharan Africa, urban clinics in India) for a variety of conditions. Similar to what we found in our study, these studies also identified technology and tools as a prominent barrier to implementation.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Several studies to date have touted the success of such interventions in reducing medication discrepancies and, in some cases, improving chronic disease control in the ambulatory setting for a wide range of conditions such as hypertension, 15,16 diabetes, 15,17 human immunodeficiency virus (HIV), 12,[18][19][20][21][22][23][24] tuberculosis (TB), 18,25 multiple myeloma, 26 and post-kidney transplantation. 15 Additionally, and importantly given the novelty of smart pillbox devices, several studies have also explored user perspectives of this technology, the majority of which have focused on patient 19,22,[27][28][29][30][31][32][33][34][35][36] rather than clinician 32,35,37 perspectives.…”
Section: Background and Significancementioning
confidence: 99%